Defining date palm leaf pruning line in bearing status by tracking physiological markers and expression of senescence-related genes - Alikhani-Koupaei, Majid (Plant physiology and biochemistry : PPB, 2021)
Copyright © 2021 Elsevier Masson SAS. All rights reserved.